Influence of Family Communication Patterns in Family Purchase Decision Making - Aggarwal, Vijita Singh; Shefali (Indian Journal of Marketing, 2019)
The purpose of the paper was to find out the influence of Indian children in family purchase decisions across product categories as per parental perception with special consideration to family communication patterns. The research was conducted on 320 parents of Delhi-NCR. Various statistical tools such as exploratory factor analysis, confirmatory factor analysis, MANOVA, multiple linear regression, and independent sample t-test were used to conduct the research. The findings concluded that Protective and Laissez-Faire type of parents had no significant influence on the purchase of product categories. The results also reported the influence of concept orientation type of communication on children’s influence in family purchase decisions across product categories, especially on child-related products and services.